Decision-making criteria for plant-species selection for phytostabilization: Issues of biodiversity and functionality. (1st October 2017) - Ellili, Ahlem; Rabier, Jacques; Prudent, Pascale; Salducci, Marie-Dominique; Heckenroth, Alma; Lachaâl, Mokhtar; Laffont-Schwob, Isabelle
Abstract: In polluted protected areas, using phytoremediation raises the question of the choice of the plant species to select. As an example, Atriplex halimus has been identified as a proliferative plant species that needs to be eradicated in the Calanques National Park (PNCal). Since it has been proven that the spontaneous populations of this plant species could phytostabilize shore waste deposits generated by past industrial activities within the PNCal territory, its status seems controversial, presenting a dilemma between biodiversity management of a protected area and ecological solutions for pollution management. To address this issue, we assessed the ability of A. halimus to grow on different soils from this territory, in order to estimate the potential invasiveness of this plant in this territory. Petri dish germinations and pot-growth experiments showed 50% germination of seeds collected on local individuals from the most polluted PNCal soil and 20% growth reduction of seedlings. Soil analysis showed that limitation of growth was caused by high pH value and sparsely available micronutrients as well as metal and metalloid contamination. Our results suggested that local populations of A. halimus may stabilize the highly metal and metalloid polluted salt-affected soils of the PNCal, with low seed germination potential lowering the eventuality of a propagation over the PNCal territory. As a consequence of this study, the administration of the PNCal decided not to remove A. halimus populations along the polluted coastline until another solution to prevent pollution dispersal had been found. This laboratory approach may be extended to other similar situations where plant species may be evaluated not only in term of phytoremediation potential but also in term of biodiversity preservation. Highlights: Though considered as potentially invasive, Atriplex halimus stabilizes heavy metals. A. halimus species spontaneously grows in polluted soils of a French National Park. A. halimus represents a good tool for ecological rehabilitation of the Park soils. Our results demonstrated low potential of dissemination by seeding in these soils. Decisional tools for biodiversity management and pollution stabilization are given.